Optimizing the Potential of Zakat to Alleviate Poverty Problems and Improve Community Economy in Surakarta City - ., Muthoifin; ., Masithoh; Yusran, Qaid Qushayyi; Afiyah, Ishmah; ., Nuha (Journal of Ecohumanism, 2024)
This study aims to determine the potential of zakat through the strategy of collecting and distributing zakat in the city of Surakarta and analyze the implementation of the role of zakat in alleviating poverty in the city of Surakarta. This type of research is field research with a qualitative approach. The research was conducted at the office of the National Amil Zakat Agency (BAZNAS) of Surakarta City. The data sources used include primary data and secondary data. The data collection techniques used in this study are observation, interviews, and documentation. Data analysis was carried out using a qualitative descriptive method. The results of the study show that the strategy of collecting and distributing zakat applied by Basnaz Surakarta City is to increase the relationship of the Zakat Collection Unit (UPZ). The target of zakat recipients is 8 Asnaf. The role of zakat in alleviating poverty in Surakarta City is realized through humanitarian programs, da’wah, advocacy, a productive economy, education, and health. The results of other studies also show that the Zakat collection and distribution strategy implemented by BAZNAS Surakarta City is to improve the relationship between the Zakat Collection Unit (UPZ). The target of zakat recipients is 8 Asnaf. The role of zakat in alleviating poverty in the city of Surakarta is realized through humanitarian programs, da’wah, advocacy, productive economy, education, and health. The novelty or originality of this research lies in the in-depth analysis of the zakat collection and distribution strategy carried out by BAZNAS Surakarta City and its influence on poverty alleviation in the region. This research provides recommendations for BAZNAS to continue to optimize the potential of zakat through increasing cooperation with UPZ and expanding the reach of community empowerment programs to achieve more equitable economic welfare in the city of Surakarta.